Design and validation of an innovative 3D printer containing a co-rotating twin screw extrusion unit - Justino Netto, Joaquim Manoel (2022)
This paper presents the design and validation of an innovative 3D printer containing a co-rotating twin screw extrusion unit (Co-TSE). Single screw print heads were developed in the mid-2000s as an alternative to filament-based 3D printers, but they have limited process flexibility and mixing capacity. The new design accepts material in powder or micro-pellet form, and its dispersive and distributive mixing capacity can be fine tuned by setting output and screw rotation speed independently. The design combines a miniaturized modular Co-TSE operated under starve-fed conditions with a benchtop Cartesian platform. Numerical calculations were performed to ascertain whether the appropriate thermomechanical environment for polymer processing could be created by the proposed design. A prototype was built and extrusion tests were performed under different operating conditions, using polypropylene and a 90/10 wt% polypropylene/polystyrene blend. Two screw configurations were used, with and without kneading discs, to assess the response of the extrusion unit in terms of flow characteristics and mixing performance. The restriction to flow created by the mixing elements determines the starting melt position, and the average residence times, while their shearing and extensional action enhances homogenization effectiveness. The screw configuration and rotation speed do not affect the output, which depends only on the feed rate. Preliminary deposition tests were conducted to determine the feasible printing parameters. A standard tensile test specimen, a square scaffold and a multicolored rectangular box were successfully printed, validating the innovative design. The mechanical properties of printed test specimens were within the expected values.